2006
DOI: 10.1007/s11469-006-9038-4
|View full text |Cite
|
Sign up to set email alerts
|

Are the Effects of Gambling Treatment Overestimated?

Abstract: Background Studies of clinical trials across the field of healthcare found use of designs that overestimate treatment effects. Objective review clinical trial designs used to develop gambling treatment evidence base for suitability to assess cause and effect and to accurately assess treatment effects. Methods literature review, grading of evidence, proportions and confidence limits Results The majority of published studies on gambling treatment are methodologically unsuited to determine treatment effects. Suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…A previous review of the problem gambling treatment literature (Westphal 2007) found lack of comparable control groups as common finding among problem gambling treatment studies. Chambless and Ollendick (2001) use type of control group as one of the study criteria for determining their three categories (well-established, possibly efficacious, and experimental) and Sackett et al (1998) also use comparable control group as one their criteria for assessment of study quality.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous review of the problem gambling treatment literature (Westphal 2007) found lack of comparable control groups as common finding among problem gambling treatment studies. Chambless and Ollendick (2001) use type of control group as one of the study criteria for determining their three categories (well-established, possibly efficacious, and experimental) and Sackett et al (1998) also use comparable control group as one their criteria for assessment of study quality.…”
Section: Methodsmentioning
confidence: 99%
“…Shaffer et al (2005) reported that only 17% of their large sample completed or substantially completed treatment. A recent review also found that gambling treatment of all types is associated with significant attrition (Westphal 2007). In a review of published gambling treatment studies from 1982 through 2005, Westphal (2007) found that attrition rates in short term pharmacological treatment studies ranged from 11.3 to 40% and in long term studies ranged from 48.3 to 59.4%.…”
Section: Attritionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serotonin reuptake inhibitors have not performed better than placebo in the double blind, placebo controlled trials among pathological gamblers while pharmacological treatments affecting other neurotransmitter systems have performed significantly better than placebo (Westphal 2007).…”
Section: Obsessive Compulsive Spectrum Modelmentioning
confidence: 99%